“EMPLOYEE ENGAGEMENT: SCORES AND INFLUENCING FACTORS CASE STUDY OF A STATE ENTERPRISE IN THAILAND” - Teera Sindecharak; Ekasit Nunbhakdi; Kanjana Boonyang; Uraiwan Runghairun (PEOPLE: International Journal of Social Sciences, 2025)
This research aims to study the engagement assessment index and analyze the factors influencing employee engagement in a state enterprise in Thailand. The study employs a quantitative research method, using a questionnaire as a data collection tool from a sample of 855 employees. Data analysis was performed using descriptive statistics (mean and standard deviation) and inferential statistics, including Multiple Regression Analysis and Structural Equation Modeling (SEM). The findings revealed that the overall employee engagement score, measured by the Employee Net Promoter Score (eNPS), indicates a need for improvement. The majority of employees fell into the ’Passive’ group (37.80%), followed by the ’Detractor’ group (33.60%), and the ’Promoter’ group (28.70%). Further analysis indicated that engagement in terms of ’Say’ was rated as excellent, ’Strive’ as good, while ’Stay’ required improvement. Factors such as organizational attitude, direct supervisors and executives, acceptance, career opportunities, welfare, and work environment positively influenced employee engagement.